2011
DOI: 10.1016/j.yexcr.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A6 contributes to the invasiveness of breast carcinoma cells by influencing the organization and localization of functional focal adhesions

Abstract: The interaction of annexin A6 (AnxA6) with membrane phospholipids and either specific extracellular matrix (ECM) components or F-actin suggests that it may influence cellular processes associated with rapid plasma membrane reorganization such as cell adhesion and motility. Here, we examined the putative roles of AnxA6 in adhesion-related cellular processes that contribute to breast cancer progression. We show that breast cancer cells secrete annexins via the exosomal pathway and that the secreted annexins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 50 publications
5
98
0
Order By: Relevance
“…The protein expression levels of AnxA6 may also be associated with BC invasiveness: Sakwe et al (34) demonstrated that AnxA6 was secreted via a Ca 2+ -dependent exosomal pathway, and the cell surface-associated AnxA6 was observed to be concentrated in the membrane protrusions of BC cells. Other studies indicated that AnxA6 acted as an adhesion receptor to fetuin-A (α2 HS-glycoprotein), a major serum adhesive protein on the surface of BC cells, by mediating growth signaling (43,44).…”
Section: Multiple Functions Of Anxa6 In Breast Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…The protein expression levels of AnxA6 may also be associated with BC invasiveness: Sakwe et al (34) demonstrated that AnxA6 was secreted via a Ca 2+ -dependent exosomal pathway, and the cell surface-associated AnxA6 was observed to be concentrated in the membrane protrusions of BC cells. Other studies indicated that AnxA6 acted as an adhesion receptor to fetuin-A (α2 HS-glycoprotein), a major serum adhesive protein on the surface of BC cells, by mediating growth signaling (43,44).…”
Section: Multiple Functions Of Anxa6 In Breast Cancermentioning
confidence: 99%
“…Other studies indicated that AnxA6 acted as an adhesion receptor to fetuin-A (α2 HS-glycoprotein), a major serum adhesive protein on the surface of BC cells, by mediating growth signaling (43,44). AnxA6 has been observed to promote the invasiveness of BT-549 BC cells, which express higher levels of AnxA6 than MCF-10A cells, since the depletion of AnxA6 in BT-549 cells reduced their motility and abolished invasiveness (34,35). AnxA6 knockdown in BT-549 BC cells (BT-A6A cells) altered their cell morphology in a dose-dependent manner, compared with parental BT-549 cells (34).…”
Section: Multiple Functions Of Anxa6 In Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations